Hemorrhagic Suprasellar Central Nervous System Embryonal Tumor in an Adult: Uncommon Features of an Extremely Rare Neoplasm - Piloni, Martina; Gagliardi, Filippo; Bailo, Michele; Barzaghi, Lina Raffaella; Callea, Marcella; Terreni, Mariarosa; Falini, Andrea; Castellano, Antonella; Mortini, Pietro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Occurrences of suprasellar central nervous system (CNS) embryonal tumors in adults are extremely rare. Hemorrhagic onset is further uncommon, with only anecdotic cases reported in the literature. The authors describe the case of a 57-year-old man affected by a suprasellar CNS embryonal tumor, with hemorrhagic onset and a unique diffusion pattern along the optic pathways.Material and Methods A 57-year-old man presenting with acute visual acuity worsening and left homonymous hemianopia was referred to our hospital. Neuroradiologic studies demonstrated an infiltrating, high-grade lesion involving the optic chiasm and right retrochiasmatic pathways with a hemorrhagic area in the ipsilateral pulvinar.Results The patient underwent microsurgical biopsy. Pathologic assessment confirmed the diagnosis of CNS embryonal tumor, not otherwise specified (NOS) according to the 2016 World Health Organization (WHO) classification of CNS tumors. The patient was referred to a multimodal adjuvant treatment; he eventually died 4 months after surgery. Competent literature has been systematically reviewed in the light of the relevant changes made in the last version of the WHO classification.Conclusion Embryonal tumors should be considered in the differential diagnosis for sellar and suprasellar space-occupying lesions, despite the rarity of the disease and the uncommon features at time of presentation. As per our knowledge, this is the first case ever described of hemorrhagic suprasellar embryonal tumor with a diffusion pattern along white matter fibers. Histogenesis, biomolecular and neuroradiologic features, and classification of embryonal tumors are an open field of research, with considerable implications for the definition of better diagnostic pitfalls and therapeutic regimens.
Keywords: adult; embryonal tumors; hemorrhage; suprasellar; supratentorial primitive neuroectodermal tumors